The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.3389/fchem.2019.00285
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Structural and Dynamic Features in Triphilic Room Temperature Ionic Liquids

Abstract: Here we report a thorough investigation of the microscopic and mesoscopic structural organization in a series of triphilic fluorinated room temperature ionic liquids, namely [1-alkyl,3-methylimidazolium][(trifluoromethanesulfonyl)(nonafluorobutylsulfonyl)imide], with alkyl = ethyl, butyl, octyl ([C n mim][IM 14 ], n = 2, 4, 8), based on the synergic exploitation of X-ray and Neutron Scattering and Molecular Dynamics simulations. This study re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 107 publications
2
18
0
Order By: Relevance
“…Although the presently considered anion is different from [TFSI] that was studied in reference 56 , we can determine that the occurrence of this HB interaction is quite rare with the present choice of cation and anion: the integrated number of neighbour anion nitrogen around the reference cation hydrogen is <0.1 for r<3 Å (corresponding to Recently, we undertook a series of investigations on a variety of AILs containing fluorous chains in their anions. 36,48,55,[57][58][59][60] Therein, we observed that, in agreement with other experimental 61 Figure 2), that typically would fingerprint the existence of segregated domains with mesoscopic spatial extent. 36,48,55,[57][58][59][60] Recently, we showed in a number of examples that while neutrons can successfully appreciate such a feature, due to contrast reasons, X-ray may fail to detect it.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Although the presently considered anion is different from [TFSI] that was studied in reference 56 , we can determine that the occurrence of this HB interaction is quite rare with the present choice of cation and anion: the integrated number of neighbour anion nitrogen around the reference cation hydrogen is <0.1 for r<3 Å (corresponding to Recently, we undertook a series of investigations on a variety of AILs containing fluorous chains in their anions. 36,48,55,[57][58][59][60] Therein, we observed that, in agreement with other experimental 61 Figure 2), that typically would fingerprint the existence of segregated domains with mesoscopic spatial extent. 36,48,55,[57][58][59][60] Recently, we showed in a number of examples that while neutrons can successfully appreciate such a feature, due to contrast reasons, X-ray may fail to detect it.…”
supporting
confidence: 91%
“…36,48,55,[57][58][59][60] Therein, we observed that, in agreement with other experimental 61 Figure 2), that typically would fingerprint the existence of segregated domains with mesoscopic spatial extent. 36,48,55,[57][58][59][60] Recently, we showed in a number of examples that while neutrons can successfully appreciate such a feature, due to contrast reasons, X-ray may fail to detect it. 36,55,[57][58][59][60]66 Neutron diffraction measurements therefore might indicate the presence of a further low Q peak centred at ca.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…172 MD simulations provided invaluable insight into how and when these domains form. [173][174][175][176][177][178][179][180] Even in cases where the liquid structure can be probed experimentally with scattering experiments, MD simulations are required to trace back the observed features to structural motifs on the molecular scale. 181,182 One of the crucial advantages here is that MD simulations based on classical force elds allow for targeted modications which are not possible experimentally.…”
Section: Machine Learning For Molecular Dynamics Simulationsmentioning
confidence: 99%
“…The structuring effect of uorinated side chains, such as lamellae formation as probed by small angle X-ray scattering, exceeds the structuring from extended alkyl side chains. [91][92][93][94] The stability of the cis conformer of [N(Ms) 2 ] À is signicantly decreased relative to [N(Tf) 2 ] À and is now 20 kJ mol À1 higher in Fluorination of anions is known to positively affect the properties of ILs, leading to lower viscosities, higher ionic conductivity, and higher diffusion, provided that the uorinated groups are not too big. 38,72,[87][88][89] It has been demonstrated here that uorination distinctively affects conformational exibility, and the properties of ILs with uorinated anions will also be a function of this exibility.…”
Section: -50mentioning
confidence: 99%